2011
DOI: 10.1155/2011/560572
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Monocyte Gene Expression in Post-Traumatic Stress Disorder

Abstract: Abstract. Post-traumatic stress disorder (PTSD) confers an increased risk for disorders with an inflammatory etiology. PTSDrelated dysregulation of the sympathetic nervous system (SNS) and hypothalamic-pituitary adrenal (HPA) axis and associated alterations in inflammatory activity may contribute to this increased risk. However, little is known about convergent SNS, HPA and inflammatory signaling at the level of the immune cell transcriptome in PTSD. To explore such signaling, we examined the prevalence of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 62 publications
5
92
1
1
Order By: Relevance
“…Compared with PBMCs from MR rhesus macaques, those from peer-reared animals (both SPR and PR) show enhanced expression of genes involved in inflammation and T-lymphocyte activation and reduced expression of genes involved in type I IFN-mediated innate antiviral responses and other pathogen-specific innate antimicrobial responses. This pattern of enhanced inflammatory gene expression and inhibited antiviral gene expression parallels the conserved transcriptional response to adversity (CTRA) observed in previous correlational studies of humans confronting adverse life circumstances (9,(27)(28)(29)(30)(31)(32)43). The experimental manipulation of early life social conditions in this study demonstrates that social adversity can play a causal role in activating CTRA dynamics and can do so during the earliest stages of postnatal immune system development.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compared with PBMCs from MR rhesus macaques, those from peer-reared animals (both SPR and PR) show enhanced expression of genes involved in inflammation and T-lymphocyte activation and reduced expression of genes involved in type I IFN-mediated innate antiviral responses and other pathogen-specific innate antimicrobial responses. This pattern of enhanced inflammatory gene expression and inhibited antiviral gene expression parallels the conserved transcriptional response to adversity (CTRA) observed in previous correlational studies of humans confronting adverse life circumstances (9,(27)(28)(29)(30)(31)(32)43). The experimental manipulation of early life social conditions in this study demonstrates that social adversity can play a causal role in activating CTRA dynamics and can do so during the earliest stages of postnatal immune system development.…”
Section: Discussionsupporting
confidence: 82%
“…To determine whether these adult transcriptional alterations might potentially stem from a biological reprogramming of the developing immune system during early life, we analyze the genome-wide transcriptional profile of circulating leukocytes in infant rhesus macaques (Macaca mulatta) after 4 mo of experimentally imposed social adversity (peer vs. maternal rearing) (26). To the extent that adverse social conditions become rapidly embedded into the gene regulatory regime of the developing immune system, we expect that (i) surrogate/peer-rearing (SPR) and peer-rearing (PR) conditions increase the expression of genes involved in inflammation while decreasing expression of genes involved in type I IFN-mediated innate antiviral responses [i.e., the "conserved transcriptional response to adversity" previously observed in adults (9,(27)(28)(29)(30)(31)(32)] and (ii) these effects are structured by transcription control pathways linked to stress-responsive "social signal transduction" pathways such as the sympathetic nervous system (SNS) and hypothalamus-pituitary-adrenal (HPA) axis (10,13,17,32). These hypotheses are tested by coupling microarray-based assessment of the entire macaque transcriptome with recent advances in computational bioinformatics (33) and multiple-hypothesis testing (34)(35)(36) to map large ensembles of differentially expressed genes into a small number of higher-order biological themes regarding their regulatory causes (e.g., transcription factor activity) (37), cellular contexts (e.g., originating leukocyte subtype) (30), and functional consequences (e.g., Gene Ontology functional annotations) (38).…”
mentioning
confidence: 99%
“…In conjunction with the analyses of transcription factor activity, these results suggest that the divergent gene expression profiles observed in hedonic and eudaimonic well-being are mediated by activation of distinct receptor systems within a fixed set of environmentally responsive cell types (33). These findings mirror results from previous studies of adverse experience in identifying a similar set of target cells (34,36,41,42), with eudaimonic well-being in particular showing a reversal of CTRA-related transcription factor dynamics (12,33). These results identify specific psychological, cellular, and molecular targets for future analyses of the social signal transduction pathways that mediate the prospective health advantages of psychological well-being (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 82%
“…Among the heterogeneous leukocyte population, bioinformatic decomposition identified monocytes and dendritic cells as most responsive to changes in socioenvironmental conditions . Analysis of isolated leukocyte subpopulations confirmed that monocytes mediate many of the transcriptional effects of social adversity, eg, of traumatic stress (O'Donovan et al, 2011), imminent bereavement, or chronic stress in caregivers of terminally ill patients (Miller et al, , 2014. Furthermore, there is evidence for a link between inflammation and early adversity (Baumeister et al, 2015).…”
Section: Introductionmentioning
confidence: 91%